2022
DOI: 10.1111/bcpt.13715
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine‐associated dose‐dependent alterations for weight and metabolic parameters in a prospective cohort

Abstract: Metabolic abnormalities have been associated with olanzapine treatment. We assessed if olanzapine has dose-dependent effects on metabolic parameters with changes for weight, blood pressure, lipid and glucose profiles being modelled using linear mixed-effects models. The risk of metabolic abnormalities including early weight gain (EWG) (≥5% during first month) was assessed using mixed-effects logistic regression models. In 392 olanzapine-treated patients (median age 38.0 years, interquartile range [IQR] = 26.0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…We did not observe a dose-dependent effect of olanzapine treatment on body weight gain. This corresponds with previous research showing that lower doses are not necessarily associated with a smaller weight gain ( 35 , 36 ). Previous studies reported that an increase in appetite plays a key role in olanzapine-induced weight gain ( 37 ).…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe a dose-dependent effect of olanzapine treatment on body weight gain. This corresponds with previous research showing that lower doses are not necessarily associated with a smaller weight gain ( 35 , 36 ). Previous studies reported that an increase in appetite plays a key role in olanzapine-induced weight gain ( 37 ).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates a high validity of our evaluation, including the results on lithium. The deleterious metabolic profile of olanzapine has been well-established in studies of varying designs (Huhn et al 2019 ; Schoretsanitis et al 2022 ), and there have been efforts to mitigate this ADR by a special drug combination, such as combining olanzapine with samidorphan (Meyer et al, 2022 ). A previous analysis of the AMSP dataset also suggested an average weight gain of 1.8 kg/week in patients treated with olanzapine (Schneider et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a high validity of our evaluation, including the results on lithium. The deleterious metabolic pro le of olanzapine has been well-established in studies of varying designs (Huhn et al, 2019;Schoretsanitis et al, 2022), and there have been efforts to mitigate this ADR by a special drug combination, such as combining olanzapine with samidorphan (Meyer et al, 2022). A previous analysis of the AMSP dataset also suggested an average weight gain of 1.8 kg/week in patients treated with olanzapine (Schneider et al, 2020).…”
Section: Discussionmentioning
confidence: 99%